Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1021/ie2020312
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Modeling of a Sequential Process for Water Treatment—Adsorption and Batch CWAO Regeneration of Activated Carbon

Abstract: A new sequential process -AD-OX -for (post)treatment of water polluted by poorly biodegradable organic compounds has been investigated. It is based on hybridizing classical adsorption on a fixed bed of activated carbon (AC) followed by batch wet catalytic oxidation at higher temperature and pressure on the same bed of AC, which is then regenerated in situ. The basic idea is to take advantage of both operations: 1-efficient water purification at room temperature by adsorption, 2-effective concentrated pollutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…It was a preliminary investigation towards a new version of the AD-OX process [36,37] by replacing wet catalytic air oxidation by photocatalysis. The water treatment was not achieved by oxidation but by adsorption, the oxidative step being needed only for pollutant degradation and subsequent AC regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…It was a preliminary investigation towards a new version of the AD-OX process [36,37] by replacing wet catalytic air oxidation by photocatalysis. The water treatment was not achieved by oxidation but by adsorption, the oxidative step being needed only for pollutant degradation and subsequent AC regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also shown that the carboxyl and hydroxyl groups inhibit the adsorption of phenol by increasing the adsorbent affinity for water. These groups have a tendency to form hydrogen bonds with the molecules water promoting their competitive adsorption and leading to the formation of true aggregates that block access of molecules pollutants to micro pores [14]. The phenomenon can be explained by the steric effect and also the difference between diffusivities of copper ions and phenol which makes copper ions more adsorbed than phenol [15].…”
Section: Adsorption Rate Of Copper Ions and Phenol On Date Rods In Mi...mentioning
confidence: 99%
“…About 7 g of catalyst was packed in a small fixed bed reactor (18 cm high and 1 cm internal diameter) for successive adsorption-oxidation cycles. The corresponding setup was described in Julcour-Lebigue et al [32]. In these assays, phenol solution (0.5 g/L) was circulated through the AC bed at 0.23 L/h until saturation of the adsorbent.…”
Section: Fixed Bed Experimentsmentioning
confidence: 99%